Development and validation of creatinine-based estimates of the glomerular filtration rate equation from chromium EDTA imaging in the multiracial Malaysian population - Wong, James; Md Ralib, Azrina; Chaw, Sook Hui; Chan, Wai Yee; Dzaharudin, Fatimah; Lily, Nicetha; Ng WS, Kevin; Shariffuddin, Ina Ismiarti (Malaysian Society of Anaesthesiology, 2025)
Introduction: The glomerular filtration rate (GFR) is a reliable parameter for assessing kidney function. It is estimated from equations such as Cockcroft–Gault (CG), Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease- Epidemiology Collaboration (CKD-EPI). However, these equations were derived using Western population demographic data and had different performances when applied to other ethnicities and populations. Objective: We developed a new equation (NE) based on the 51Cr-EDTA-measured GFR, that can be used explicitly in the Malaysian multiracial population. Methods: A cross-sectional study was conducted using electronic medical records of patients who underwent 51Cr-EDTA imaging between 2013 and 2021. Ethical approval was obtained. Results: A total of 209 patients were recruited, of which 105 patients were randomised to the development cohort and 104 patients to the validation cohort. The NE was developed using the development cohort data, and its performance was subsequently tested in the validation cohort. The result showed that CKD-EPI had the highest precision and accuracy in estimating GFR. CG had the lowest bias, while the NE performed second best. CKD-EPI had the highest correlation to 51Cr-EDTA imaging-measured GFR, followed by the NE. Conclusion: CKD-EPI demonstrated the best performance among the estimated GFR equations. However, NE showed comparable performance, exhibiting low bias, high precision, and good accuracy.